(untitled) (Journal of Universal Science Research, 2023)
This article delves into the intricate relationship between psycholinguistics and simultaneous interpreting, exploring the cognitive processes, linguistic mechanisms, and challenges involved. It examines how interpreters navigate between languages, elucidating the psychological aspects that influence their performance. The article discusses key concepts in psycholinguistics and their application in simultaneous interpreting, shedding light on the complexities and cognitive demands faced by interpreters in their practice.